The Growth Performance of Tilapia (Oreochromis sp.) using Different Doses of Organic Cooper (Cu–O) in the Diets - Dedi Jusadi; Yessy Rahmayanti; Muhammad Raditya Gumelar; Talita Shofa Adestia; Muhammad Agus Suprayudi (Journal of Aquaculture and Fish Health, 2026)
Copper (Cu-O) is a micromineral required in small amounts in the body, yet it plays an important role in the metabolism and health of fish. This study aimed to evaluate the growth performance of tilapia (Oreochromis sp.) fed diets supplemented with organic copper (Cu-O). Four treatments were tested: K (control, without Cu-O), Cu-O 1 (1 mg kg⁻¹ Cu-O), Cu-O 2 (2 mg kg⁻¹ Cu-O), and Cu-O 3 (3 mg kg⁻¹ Cu-O). Fifteen tilapia with an average initial weight of 8.75 ± 0.02 g were reared in aquaria (60 × 50 × 40 cm, water depth 30 cm) for 60 days. Fish were fed to satiation three times daily. The results showed that the growth parameters of tilapia fed Cu-O-supplemented diets were significantly higher (P < 0.05) than those of the control. The optimal dose of Cu-O supplementation was found to be 2 mg kg⁻¹ feed; subsequent studies should investigate interspecies variations and refine dosage recommendations accordingly.